Sex life dissatisfaction contribute to intention toward infidelity among Malaysians: relationship satisfaction as a mediator - Soon Aun Tan; Siew Mun Ang; Pit Wan Pung; Xi Yao Teoh; Seow Ling Ooh (BMC Psychology)
Abstract Background Intention toward infidelity or extramarital affairs could be caused by sex life dissatisfaction and low relationship satisfaction. Although sex is just a tiny part of a marriage’s relationship, the importance of sex life in a relationship cannot be easily underestimated. Past studies have found some important associations between sex life and relationship satisfaction in determining whether a person would decide to engage in marital infidelity. Nonetheless, the underlying mechanism of the association between sex life satisfaction and intention toward infidelity is unexplored in the Malaysian context. Therefore, this study aimed to examine the mediating role of relationship satisfaction in its direct association between sex life satisfaction and intention toward infidelity among Malaysian married individuals. Method A total of 292 married individuals (Mage=42.98; SDage=9.82; 66.4% women; 65.4% Chinese Malaysians, 15.8% Indians Malaysians, 14.7% Others Ethnic Malaysians, and 4.1% Malay Malaysians) participated in the cross-sectional quantitative online survey. Results A significant positive association was found between sex life and relationship satisfaction. However, sex life and relationship satisfaction were negatively associated with intention toward infidelity. Meanwhile, relationship satisfaction significantly mediates the link between sex life satisfaction and intention toward infidelity after controlling for the effects of age and gender. These findings support the hypothetical mediating role of relationship satisfaction in the association between sex life satisfaction and intention toward infidelity. Conclusions This study may fill a knowledge gap in Malaysia about the underlying association among these variables as well as the practical implication of the importance of sex life and relationship satisfaction in determining whether one would engage in extramarital affairs.